Innovating to Reduce Risk : The Case of Livestock Insurance in Mongolia - Belete, Nathan (World Bank, Washington, DC, 2012)
The Mongolia Index Based Livestock Insurance Project (P088816) is piloting insurance plans in three provinces, Bayankhongor, Uvs, and Khenti. It consists of five components. The first provides the mechanism to pilot two index-based livestock insurance (IBLI) products. The second component of the project entails a variety of targeted promotional and public awareness activities to foster awareness and inform stakeholders about the details of the two products and the IBLI pilot. The third component supports the institutional framework and capacity necessary to expand the availability of the insurance products once the viability of IBLI instruments has been established. The fourth component monitors a variety of stakeholders during the IBLI pilot in tracking access by different social groups, monitoring how the two products are received, and in determining whether herders modify their behavior in response and, if so, how their behavior changes. The project's fifth component supports the project implementation unit in its management functions. The lessons learned also suggest themselves as potentially replicable by other project teams, and as warranting the attention of other governments that seek to manage the risks faced by livestock-dependent communities.